Synthesis, Crystal Structures and Hirshfeld Surface Analysis of Coordination Compounds (Volume II) - Maniukiewicz, Waldemar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The special issue of Crystals entitled "Synthesis, Crystal Structures and Hirshfeld Surface Analysis of Coordination Compounds" (Volume II) resulted in the publication of 13 articles. The chemistry of coordination compounds plays a vital role in various areas of science, including inorganic chemistry, biochemistry, catalysis, materials science, and medicine. The main goal of this edition was the synthesis of new complex compounds with interesting properties. In order to achieve this goal, it was important to know the crystal structure and intermolecular interactions described by Hirshfeld surfaces. The crystal structure analysis plays a crucial role in predicting and correlating material properties and designing new materials. Whereas the Hirshfeld analysis provides valuable insights into the interactions between atoms in a crystal structure. It can be used to quantify and visualize intermolecular contacts, hydrogen bonding patterns, and other types of non-covalent interactions. Additionally, it can also help understand the effects of crystal packing on molecular properties, such as charge transfer, electrostatic interactions, and deformation of electron density. Overall, the chemistry of coordination compounds provides a rich framework for understanding and manipulating the properties and behavior of various substances. Its significance spans across different scientific disciplines, contributing to advancements in technology, medicine, and our understanding of the natural world. I hope, that readers will find interesting articles in this special issue of Crystals.